Analisis problematika guru dalam mengimplementasikan pilar deep learning pada pembelajaran PAI - Putra, Bagas Adi; Abdan, Muhammad Rohmad; Hidayati, Fithri (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study aims to analyze the problems faced by Islamic Religious Education (PAI) teachers in implementing the pillars of deep learning—comprising mindful learning, meaningful learning, and joyful learning at SMK Negeri Pringkuku. This approach has become increasingly relevant amidst educational transformation demands that require students to not only memorize theory but also to deeply understand meanings and apply religious values within real-life contexts and the professional world. This research employs a descriptive qualitative method with a case study design. Data were gathered through participatory observation, in-depth interviews with the Vice Principal of Curriculum, PAI teachers, and students, as well as document analysis. The results indicate that although teachers have attempted to integrate mindfulness through spiritual routines and by linking material to vocational competencies, implementation still faces multidimensional obstacles. The primary problems include: 1) the heterogeneity of students' religious backgrounds and low initial understanding; 2) limited time allocation for conducting deep reflection; 3) students' physical exhaustion due to heavy vocational practice loads; and 4) the challenges faced by teachers in synchronizing theological material with the specific realities of various vocational majors. This study recommends the necessity of specialized pedagogical training for PAI teachers in vocational schools to enable them to design more adaptive and contextual learning strategies. Abstrak Penelitian ini bertujuan untuk menganalisis problematika yang dihadapi guru Pendidikan Agama Islam (PAI) dalam mengimplementasikan pilar-pilar deep learning yang meliputi mindful learning, meaningful learning, dan joyful learning di SMK Negeri Pringkuku. Pendekatan ini menjadi relevan di tengah tuntutan transformasi pendidikan yang mengharuskan siswa tidak hanya menghafal teori, tetapi juga mendalami makna dan menerapkan nilai-nilai agama dalam konteks kehidupan nyata dan dunia kerja. Penelitian ini menggunakan metode kualitatif deskriptif dengan desain studi kasus. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan Waka Kurikulum, guru PAI, dan siswa, serta analisis dokumen. Hasil penelitian menunjukkan bahwa meskipun guru telah berupaya mengintegrasikan elemen mindfulness melalui rutinitas spiritual dan mengaitkan materi dengan kompetensi kejuruan, implementasinya masih menghadapi hambatan multidimensional. Problematika utama mencakup: 1) heterogenitas latar belakang pemahaman agama siswa yang rendah; 2) keterbatasan alokasi waktu untuk melakukan refleksi mendalam; 3) kelelahan fisik siswa akibat beban praktik kejuruan; dan 4) tantangan guru dalam menyinkronkan materi teologis dengan realitas spesifik berbagai jurusan. Penelitian ini merekomendasikan perlunya pelatihan pedagogi khusus bagi guru PAI di sekolah vokasi agar mampu merancang strategi pembelajaran yang lebih adaptif dan kontekstual.